Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsami.7b18304
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Magnetic Structure of the Ferritin Core during Iron Loading and Release by Magnetooptical and NMR Methods

Abstract: Ferritins are proteins, which serve as a storage and transportation capsule for iron inside living organisms. Continuously charging the proteins with iron and releasing it from the ferritin is necessary to assure proper management of these important ions within the organism. On the other hand, synthetic ferritins have great potential for biomedical and technological applications. In this work, the behavior of ferritin during the processes of iron loading and release was examined using multiplicity of the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
(139 reference statements)
1
15
0
Order By: Relevance
“…Interestingly, the iron oxide NPs inside E2-LFtn are dominated by Fe II rather than Fe III ions as reported for ferritin. 54,55 This observation suggests that the iron mineralisation process in E2-LFtn differs from that of ferritin which could be related to the differences in cavity size and spatial arrangement of the M-ferritin mimicking catalytic sites. 22 The ratio of the peak areas (R I = Fe II /Fe III ) for 3000Fe E2-LFtn decreases with decreasing T from 1.25 at 300 K to 0.50 at 120 K (Fig.…”
Section: Characterisation Of Iron Oxide Nps Inside E2-lftnmentioning
confidence: 95%
“…Interestingly, the iron oxide NPs inside E2-LFtn are dominated by Fe II rather than Fe III ions as reported for ferritin. 54,55 This observation suggests that the iron mineralisation process in E2-LFtn differs from that of ferritin which could be related to the differences in cavity size and spatial arrangement of the M-ferritin mimicking catalytic sites. 22 The ratio of the peak areas (R I = Fe II /Fe III ) for 3000Fe E2-LFtn decreases with decreasing T from 1.25 at 300 K to 0.50 at 120 K (Fig.…”
Section: Characterisation Of Iron Oxide Nps Inside E2-lftnmentioning
confidence: 95%
“…So far, side-chain conformational changes in the amino acid that interacts with Au +3 or Au 0 have been reported [28,51]. In addition, different authors have reported the conservation of the secondary structures of ferritin after iron incorporation to produce magnetoferritin, therefore maintaining the almost intact protein cage after iron mineralization [56][57][58][59]. Identical results were reported by Xiangyou Lui et al, revealing that ferritin with Pt nanoparticles does not have significant changes in the secondary structures of the protein, markedly α-helical [60].…”
Section: Gold Nanoparticles Synthesis and Characterizationmentioning
confidence: 99%
“…In case of the ferritin protein, the CD spectrum showed bands at 222 nm (ellipticity: -42.9 ± 5.7 mdeg), 203.9 nm (ellipticity: -24.3 ± 11 mdeg) and 197.9 nm (ellipticity: 8.2 ± 3 mdeg) (Fig 1B, black curve). The shape of the curve and magnitude of these far UV-CD bands suggest that ferritin protein has a substantial helical content and the polypeptide chains exist in an ordered structure [48,49]. For the protease-treated holoferritin, the bands observed at 222.1 nm, 202.8 nm and 198 nm (Fig 1B , red curve) indicate minimal shift in the band positions, although the ellipticity values, i.e., -30.7 ± 0.8 mdeg, -28.7 ± 2 mdeg and 14.6 ± 9 mdeg for the bands at 222.1 nm, 202.8 nm and 198 nm, respectively, are significantly altered.…”
Section: Plos Onementioning
confidence: 99%